Cover Crop Effect on Subsequent Wheat Yield in the Central Great Plains. (1st January 2016) - Nielsen, David C.; Lyon, Drew J.; Higgins, Robert K.; Hergert, Gary W.; Holman, Johnathon D.; Vigil, Merle F.
Abstract : Crop production systems in the water‐limited environment of the semiarid central Great Plains may not have potential to profitably use cover crops because of lowered subsequent wheat ( Triticum asestivum L.) yields following the cover crop. Mixtures have reportedly shown less yield‐reducing effects on subsequent crops than single‐species plantings. This study was conducted to determine winter wheat yields following both mixtures and single‐species plantings of spring‐planted cover crops. The study was conducted at Akron, CO, and Sidney, NE, during the 2012–2013 and 2013–2014 wheat growing seasons under both rainfed and irrigated conditions. Precipitation storage efficiency before wheat planting, wheat water use, biomass, and yield were measured and water use efficiency and harvest index were calculated for wheat following four single‐species cover crops (flax [ Linum usitatissimum L.], oat [ Avena sativa L.], pea [ Pisum sativum ssp. arvense L. Poir], rapeseed [ Brassica napus L.]), a 10‐species mixture, and a fallow treatment with proso millet ( Panicum miliaceum L.) residue. There was an average 10% reduction in wheat yield following a cover crop compared with following fallow, regardless of whether the cover crop was grown in a mixture or in a single‐species planting. Yield reductions were greater under drier conditions. The slope of the wheat water use–yield relationship was not significantly different for wheat following the mixture (11.80 kg ha −1 mm −1 ) than for wheat following single‐species plantings (12.32–13.57 kg ha −1 mm −1 ). The greater expense associated with a cover crop mixture compared with a single species is not justified.